Prediction of pressure ulcer development in hospitalized patients: a tool for risk assessment. Issue 1 (2nd February 2006) - Schoonhoven, L; Grobbee, D E; Donders, A R T; Algra, A; Grypdonck, M H; Bousema, M T; Schrijvers, A J P; Buskens, E
Abstract : Objectives: To identify independent predictors for development of pressure ulcers in hospitalized patients and to develop a simple prediction rule for pressure ulcer development. Design: The Prevention and Pressure Ulcer Risk Score Evaluation (prePURSE) study is a prospective cohort study in which patients are followed up once a week until pressure ulcer occurrence, discharge from hospital, or length of stay over 12 weeks. Data were collected between January 1999 and June 2000. Setting: Two large hospitals in the Netherlands. Participants: Adult patients admitted to the surgical, internal, neurological and geriatric wards for more than 5 days were eligible. A consecutive sample of 1536 patients was visited, 1431 (93%) of whom agreed to participate. Complete follow up data were available for 1229 (80%) patients. Main outcome measures: Occurrence of a pressure ulcer grade 2 or worse during admission to hospital. Results: Independent predictors of pressure ulcers were age, weight at admission, abnormal appearance of the skin, friction and shear, and planned surgery in coming week. The area under the curve of the final prediction rule was 0.70 after bootstrapping. At a cut off score of 20, 42% of the patient weeks were identified as at risk for pressure ulcer development, thus correctly identifying 70% of the patient weeks in which a pressure ulcer occurred. Conclusion: A simple clinical prediction rule based on five patient characteristics may help to identify patients at increased risk for pressure ulcer development and in need of preventive measures.